A Knockout of the Tsg101 Gene Leads to Decreased Expression of ErbB Receptor Tyrosine Kinases and Induction of Autophagy Prior to Cell Death - Morris, Chantey R. (Public Library of Science, 2012)
The Tumor Susceptibility Gene 101 (Tsg101) encodes a multi-domain protein that mediates a variety of molecular and biological processes including the trafficking and lysosomal degradation of cell surface receptors. Conventional and conditional knockout models have demonstrated an essential requirement of this gene for cell cycle progression and cell viability, but the consequences of a complete ablation of Tsg101 on intracellular processes have not been examined to date. In this study, we employed mouse embryonic fibroblasts that carry two Tsg101 conditional knockout alleles to investigate the expression of ErbB receptor tyrosine kinases as well as stress-induced intracellular processes that are known to be associated with a defect in growth and cell survival. The conditional deletion of the Tsg101 gene in this well-controlled experimental model resulted in a significant reduction in the steady-state levels of the EGFR and ErbB2 but a stress-induced elevation in the phosphorylation of mitogen activated protein (MAP) kinases independent of growth factor stimulation. As part of an integrated stress response, Tsg101-deficient cells exhibited extensive remodeling of actin filaments and greatly enlarged lysosomes that were enriched with the autophagy-related protein LC3. The increase in the transcriptional activation and expression of LC3 and its association with Lamp1-positive lysosomes in a PI3K-dependent manner suggest that Tsg101 knockout cells utilize autophagy as a survival mechanism prior to their ultimate death. Collectively, this study shows that a knockout of the Tsg101 gene causes complex intracellular changes associated with stress response and cell death. These multifaceted alterations need to be recognized as they have an impact on defining particular functions for Tsg101 in processes such as signal transduction and lysosomal/endosomal trafficking.